ANALISIS PENGELOLAAN DANA PENSIUN DAN PENDISTRIBUSIAN HAK WARIS HNWI Studi Kasus pada Klien X - , Novi Yuningsih ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia has good prospects for the financial services sector businesses such as wealth management which began to emerge at the beginning of the 2000s. Wealth Management is derived from science of finance, it offers very interesting financial management service to answer the needs of the users and one of them is HNWIs (High Net worth Individuals) with minimum net worth US$1 million and maximum net worth US$30 millions. The third pillar Wealth Management learns how to deal with transitions or retirements with an allocation of assets which held by HNWIs and distribute assets to heirs. The purpose of this study was to determine the client's risk profile based on risk tolerance in order to find the right investment instruments to client, to analyze clientâs portfolio and to provide alternative solutions to client problems in which related to the preparation of pension funds. This study also to analyze clientâs assets that can be allocated for distribution to heirs. This research used single case study that require a client as object of research. The case study taken from a family included in the category of high net worth individuals. The author intends to anylize financial and risk profile of the client, so that author can provide the best recommendation for their retirement plan. The author used these steps for analyse techniques: client profiling, financial statement analysis, create a pension plan by calculate pension funds using expenses method and sensitivity analysis with two scenarios. The results of this research indicate that changes in clientâs investment portfolio, which described in scenario II, would be the right choice for retirement planning and distribution of client assets.